Słońce i cień. Dramaturgia Posłańca: Hartley / Pinter / Losey - Katafiasz, Olga (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Sun and Shadow; The Go-Between’s Dramaturgy: Hartley / Pinter / Losey The text explores the dramaturgy of Leslie Poles Hartley’s novel The Go-Between (1953) and its adaptations: Harold Pinter’s screenplay and Joseph Losey’s movie (The Go-Between, 1971). Th e author analyzes some decisions made by the authors of the novel, screenplay and movie about the roles assigned to them and to the audience which are crucial for the dramaturgy of The Go-Between. Following on from this, eff orts to subjectivize the narration turn out to be essential, as well. The author also emphasizes the unusually important play with time in the narration and its consequences for the characters’ construction and the way they are judged. A matter of great importance in Losey’s movie work, which is a variant of Hartley’s novel and at the same time of Pinter’s screenplay, is the method of its frame semantics creation. As far as the novel is concerned, the author analyzes the roles of the narrator and the reader, who has to put facts in order (as the chronology is distorted) and make judgments about them. Equally important in determining the novel’s dramaturgy are symbolism of light and shadow, as well as the fact that its plot is set in 1900. In his screenplay, Pinter doesn’t directly mention the time of action; instead he identifies it as the “past”, “present” and “time neutral”. His screenplay is based on two dramaturgic principles: the splitting of Leo Colston’s character (the audience doesn’t perceive the child and the adult as the same person) and the introduction of narrative disruptions in the form of “present” scenes. Joseph Losey made a few significant changes to the screenplay. The most important of these seems to be the removal of all the scenes not featuring Leo, which makes him the sole narrator. Clearly defining the presented world in the movie is the opposition between light and shadow, which is distinct in the frame composition. It turns out that equally important for the dramaturgy of Losey’s Th e Go-Between is Michael Redgrave, who was cast in the role of Colston, and how he creates this character.